Kajian Penggunaan Metode Mean Annual Flood (MAF), Rasional, Der Weduwen Dan Haspers Untuk Menentukan Debit Banjir Pada Sub Das Cikeruh - Yessi Carolina; Edy Suryadi; Dwi Rustam Kendarto (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2022)
Water is an essential thing for every living creature. However, it can cause several problems, namely floods, droughts, and water pollution. The Cikeruh sub-watershed area is frequently flooded, especially in the Rancaekek and Bojongsoang sub-districts, causing damage to public facilities and infrastructure and property losses. Therefore, a flood discharge analysis is carried out to determine the magnitude of the planned flood discharge in the Cikeruh sub-watershed. This study aims to obtain the deviation of the planned flood discharge value using the Mean Annual Flood method, the Rational method, the Der Weduwen method and the Haspers method with the planned flood discharge with measured data. This study uses a literature study and analyzes the frequency of the maximum precipitation to obtain the planned flood discharge in the Cikeruh sub-watershed. The results of the calculation of precipitation data using the Mean Annual Flood, Rational, Der Weduwen and Haspers methods on the frequency analysis of the measured discharge data is the smallest deviation occurs against the Mean Annual Flood method, which is 20.98% for the 2-year return period, 17.47% for the 5-year return period, 27.22% for 10-year return period, 42.68% for 20-year return period, 62.68% for 50 year return period, and 83.87% for 100 year return period. The results of this study are useful to know the methods that can be used as a reference in calculating the flood discharge plan and taken into consideration in planning the construction of waterworks.